Facts about Vitamin K - R. Elaine Turner (EDIS)
Revised! FCS-8666, a 2-page fact sheet by R. Elaine Turner, has been updated with new graphics and revised figures for the amount of vitamin K in common foods. Published by the UF Department of Family Youth and Community Sciences, April 2006.